Optimisation studies of the TAIGA-Muon scintillation detector array. (1st June 2022) - ,; Astapov, I.; Bezyazeekov, P.; Blank, M.; Bonvech, E.; Borodin, A.; Brueckner, M.; Budnev, N.; Bulan, A.; Chernov, D.; Chiavassa, A.; Dyachok, A.; et al.
Abstract: The TAIGA astroparticle observatory is progressing with the deployment of new detector stations. The Tunka-Grande — scintillation counter array of the observatory expands with the new TAIGA-Muon stations. Several simulation studies were conducted for optimisation of the new station positioning and performance. Extensive air showers induced by gamma quanta or a proton in the range from 100 TeV to 1 PeV at a zenith angle of 0° were used for these studies. Based on the developed simulation, the capabilities of identification of high energy extensive air showers were studied. The soil thickness, the detector and station positions, the lowest measurable energy range of the cosmic rays, and different methods of air shower identification were investigated.